Auditoría del rubro ingresos – cuentas por cobrar de una compañía que se dedica a la producción y comercialización de cartón por el año terminado el 31 de diciembre del 2007 en la ciudad de durán. - Sanabria Santillán, María Del Carmen (2010)
The information set forth in the financial statements is of paramount importance for organizations, today there any entity that does not need this information for quick and appropriate decisions. The financial information represents the factor of success of a company, because if it is presented incorrectly will not only affect the components but also to companies related to it, whether customers or suppliers. Based on raised as soon as this work is done with information from a company that is dedicated to the production and marketing of cardboard, to be used with the objective of the audit of the revenue item - accounts receivable for the year ended December 31, 2007 in the city of Durham. In the present study is seen next steps for conducting the audit, business knowledge, organizational structure, accounting policies, mission, vision, policies, etc. Likewise, the knowledge and internal evaluation, the strategy and audit procedures used, results of tests applied, the conclusions and recommendations. In conclusion, the revelation of the income item - Accounts Receivable in the financial statements is reasonable and consistent with accounting principles generally accepted auditing standards.